Rancang Bangun Kanula Hidung Aliran Tinggi dilengkapi Sistem Humidifikasi untuk Hipoksemik Akut - Ernia Susana; Indah Nursyamsi Handayani; Agus Komarudin (Diponegoro University, 2022)
High-Flow Nasal Cannula (HFNC) is a non-invasive oxygen therapy device that aids in administering high-flow oxygen to patients with acute respiratory distress syndrome. Since the end of 2019, the worldwide demand for HFNC devices has risen dramatically because of the Covid-19 outbreak. Multiple studies have endorsed HFNC as a treatment strategy for individuals in the early infection phase (stage 1) until they enter the pulmonary phase (pulmonary phase). Therefore, in anticipation of the need for these devices, the Indonesian Ministry of Health encourages the development of HFNC as a step towards self-sufficiency in domestic medical device products. This article describes the design of an HFNC prototype based on components accessible on the local market and a software system based on open source. The research design uses engineering design. The HFNC device is intended to create a fraction of inspired oxygen (FiO 2) in the range of 30-100%, which is regulated by two settings: oxygen flow rate and compressed air. The test results demonstrate that the FiO 2 correction value satisfies the HFNC product test method requirements of less than 5% Oxygen for every air flow rate and compressed air setting. In addition, the airflow rate measurement meets the threshold value of 60 lpm. Based on testing using performance measurement tools, it can be concluded that the HFNC design can be used as a therapeutic tool for acute hypoxia.